PUTUSAN ULTRA PETITA DALAM TINDAK PIDANA NARKOTIKA BERDASARKAN UNDANG-UNDANG NARKOTIKA - Hafizhah Azzahra; Setiyono (Fakultas Hukum Universitas Trisakti, 2022)
The case that occurred on February 1st, 2019 involved a sale and purchase transaction of methamphetamine by Boiy Sairy alias Busairi Bin Tomin. The decision from the Panel of Judges of Situbondo District Court is different from the article charged by the public prosecutor in a single indictment. The defendant was charged with Article 112 of the Narcotics Law, while the judges gives a decision under Article 127 of the Narcotics Law. This research is normative and descriptive analytical legal research, using secondary data obtain through litearure studies and interviews. The data is analyzed qualitatively and conclusions are drawn using deductive understanding. The conclusion of the research is that the Judges use Article 127 while in the indictment and the facts of the trial and the jurisprudence of the Supreme Court Decision No. 675 K/Pid/1987, the Defendant BS was proven to have abused Narcotics so that the Judge imposed a criminal sentence and this decision has permanent legal force so that it is valid in the eyes of the law.